Patient isolation for infection control and patient experience. (18th December 2018) - Siddiqui, Zishan K.; Conway, Sarah Johnson; Abusamaan, Mohammed; Bertram, Amanda; Berry, Stephen A.; Allen, Lisa; Apfel, Ariella; Farley, Holley; Zhu, Junya; Wu, Albert W.; Brotman, Daniel J.
Abstract: Objective: Hospitalized patients placed in isolation due to a carrier state or infection with resistant or highly communicable organisms report higher rates of anxiety and loneliness and have fewer physician encounters, room entries, and vital sign records. We hypothesized that isolation status might adversely impact patient experience as reported through Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) surveys, particularly regarding communication. Design: Retrospective analysis of HCAHPS survey results over 5 years. Setting: A 1, 165-bed, tertiary-care, academic medical center. Patients: Patients on any type of isolation for at least 50% of their stay were the exposure group. Those never in isolation served as controls. Methods: Multivariable logistic regression, adjusting for age, race, gender, payer, severity of illness, length of stay and clinical service were used to examine associations between isolation status and "top-box" experience scores. Dose response to increasing percentage of days in isolation was also analyzed. Results: Patients in isolation reported worse experience, primarily with staff responsiveness (help toileting 63% vs 51%; adjusted odds ratio [aOR], 0.77; P = .0009) and overall care (rate hospital 80% vs 73%; aOR, 0.78; P < .0001), but they reported similar experience in other domains. No dose-response effect was observed. Conclusion: Isolated patients do not report adverse experience for most aspects of provider communication regarded to be among the most important elements for safety and quality of care. However, patients in isolation had worse experiences with staff responsiveness for time-sensitive needs. The absence of a dose-response effect suggests that isolation status may be a marker for other factors, such as illness severity. Regardless, hospitals should emphasize timely staff response for this population.